2001
DOI: 10.1067/mtc.2001.111377
|View full text |Cite
|
Sign up to set email alerts
|

Pleuroperitoneal shunts and tumor seeding

Abstract: A 76-year-old man with malignant mesothelioma of the left pleura was referred for surgical palliation. He was dyspneic at rest and had anterior chest pain and a persistent cough. Chest x-ray film revealed an extensive left pleural effusion. A thoracoscopy was performed, and 3L of pleural fluid was drained. Both the pleural surfaces and rhe diaphragm were studded with tumors. On maximal inflation of the lung, the parietal and visceral pleura did not oppose, and therefore a Denver shunt was inserted. At 6 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For these patients, a pleuro-peritoneal shunt is a better palliative choice. [26][27][28] We have placed pleuroperitoneal shunts in seven patients, all with success.…”
Section: Discussionmentioning
confidence: 94%
“…For these patients, a pleuro-peritoneal shunt is a better palliative choice. [26][27][28] We have placed pleuroperitoneal shunts in seven patients, all with success.…”
Section: Discussionmentioning
confidence: 94%
“…12,13 Pleuroperitoneal shunting was suggested for trapped lung, but high morbidity, shunt failure, translocation of tumor cells into the peritoneal cavity, and less patient compliance limited its widespread use. 11,13,14 We previously used a Denver shunt for MPE associated with trapped lung and found that patients had diffi culties in using the shunts. We agree with Bernard and colleagues 9 that thoracotomy for decortication/pleurectomy for trapped lung should be avoided in patients with limited life expectancy as it has been associated with prolonged air leak, longer hospital stay, 23% morbidity and 10% hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of seeding alongside peritoneovenous shunts and pleuroperitoneal shunts; however, none of these were seen in metastatic breast cancer. 9 She has been closely followed with Positron emission tomography (PET) scans, with no evidence of intra-abdominal metastatic disease. Before shunt placement, the patient had multiple workups for infectious and neoplastic processes, including cytology for breast implant–associated anaplastic large cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%